Contributions to understanding adenylate kinase and myristoylation reactions in the malaria parasite Plasmodium falciparum - Ma, Jipeng; Justus Liebig University Giessen (My University, 2012)
Malaria remains a fatal tropical disease caused by a protozoan known as Plasmodium and is threatening almost half the world´s population. Due to the absence of effective malaria vaccines and remarkable increase of drug resistance, the deep understanding of parasite biology and identification of new drug targets are desperately required. In this thesis, three aspects have been studied to better understand the energy metabolism of Plasmodium falciparum and to support the search for new potential drug targets.First, two new adenylate kinase-like proteins have been successfully overexpressed in E. coli cells and purified via affinity chromatography. Different substrates of nucleoside triphosphate and monophosphate were used for determining the enzyme activity. However, PfAKLP1 (Plasmodium falciparum adenylate kinase-like protein 1) only exhibited low activity with ATP and AMP as substrates in the enzymic assay in vitro while there was no detectable activity for recombinant PfAKLP2 (Plasmodium falciparum adenylate kinase-like protein 2). Besides, we also investigated the subcellular localization of all five adenylate kinases characterized from Plasmodium falciparum systematically by fusing GFP to the respective adenylate kinase. PfAK1, PfAKLP1, and PfAKLP2 were all shown to be localized in the cytosol of the parasites while PfGAK which only showed high activity with GTP as substrate was found to be in the mitochondrion. Interestingly, PfAK2, a unique myristoylated adenylate kinase, was demonstrated to be targeted to the PVM (parasitophorous vacuole membrane). A mutation in the myristoylation site of PfAK2 could entirely change the subcellular localization from PVM to cytosol, showing that myristoylation is responsible for such localization. Results from Western blots using the transfected parasite lysate could confirm the membrane associated localization of PfAK2. Unlike adenylate kinase in other species, no adenylate kinase which utilized ATP as substrate was localized in the mitochondrion. This might indicate that the mitochondrion is not the main source of ATP in Plasmodium, also taking into account that a novel branched tricarboxylic acid pathway was demonstrated. These findings enhance our knowledge on adenylate kinase isoforms and energy metabolism mediated by adenylate kinase in Plasmodium falciparum.Secondly, an overexpression and purification method for recombinant PfNMT with relatively high yield and purity was established. More than 500 crystallization solutions were tested to obtain the promising conditions for PfNMT crystallization. At least two conditions were further studied to crystallize PfNMT. Although no high quality crystals have been obtained so far, the screening seems to be worth of further optimization. To gain first structural insights, a model of PfNMT was acquired based on the structure of NMT from Plasmodium vivax which showed 80% identity in the amino acid sequence. By comparison the model of PfNMT with the structure of human NMT1, differences in two regions related to the peptide substrate binding were observed, which may provide the basis for selective inhibition of NMT.Thirdly, a metabolic labeling method was applied to study protein myristoylation in P. falciparum. The myristoylated proteins were metabolically labeled by a myristic acid analogue and further biotinylated via the so-called click reaction. The myristoylated proteins could then be detected by a streptavidin-HRP blot. The avidin beads were used to enrich the target proteins so as to identify these targets by mass spectrometry. Furthermore, two bioinformatic tools for myristoylation prediction based on the conserved myristoylation motif were used to predict the potential targets in the whole proteome. As a result, 42 proteins were assumed to be myristoylated by the MYR Predictor tool and 64 proteins were discovered by the Myristoylator tool. Although it was possible to predict the myristoylated proteins from their amino acid sequences, the results from the two bioinformatic tools compared with the experimentally identified targets implied that some real targets might be easily overlooked by the bioinformatic approaches. Therefore, the metabolic labeling study is a beneficial method not only to understand the biological pathways involved in myristoylation but also to discover novel myristoylated proteins from P. falciparum.

Die tropische Erkrankung Malaria wird durch Plasmodium verursacht und bedroht nahezu die Hälfte der Weltbevölkerung. Aufgrund fehlender Malariavakzine und steigenden Resistenzen gegen vorhandene Medikamente, ist es wichtig, die Biologie des Parasiten besser zu verstehen und neue Medikamentezuentwickeln. In dieser Dissertation wurden drei Aspekte untersucht, um den Energiestoffwechsel des Parasiten besser zu verstehen und nach neuen möglichen Medikamentenzielen zu suchen.Zwei neue Adenylatkinase-ähnliche Proteine wurden erfolgreich in E. coli-Zellenüberexprimiert und mittels Affinitätschromatographie gereinigt. PfAKLP1 (P. falciparumAdenylatekinase-ähnliches Protein 1) zeigte in den enzymatischen Assayseine geringe Aktivität mit den Substraten ATP und AMP, während für PfAKLP2 keine Aktivität zu messen war. Weiterhin untersuchte ich die subzelluläre Lokalisation von allen 5 bisher bekannten Adenylatkinasen aus P.falciparum systematisch durch den Einsatz von GFP-gekoppelten Adenylatkinase-Konstrukten. PfAK1, PfAKLP1 und PfAKLP2 ließen sich imParasitenzytosol nachweisen, während PfGAKim Mitochondrium lokalisiert werden konnte. Interessanterweise wurdePfAK2, die eine einzigartige myristoylierteAdenylatkinase darstellt, in der PVM (parasitophorousvacuolemembrane) gefunden. Eine in die Myristoylierungsstelle von PfAK2 eingefügte Mutation konnte die subzelluläre Lokalisation vollständig von der PVM in das Zytosol verschieben und zeigte somit, dass die Myristyolierung für diese Lokalisation verantwortlich ist. Western Blot-Untersuchungen mit dem Lysatinfizierter Parasiten konnten die Membran-Assoziation bestätigen.Zweitens wurdeein Überexpressions- und Reinigungsprotokoll für die Herstellung rekombinanter P.falciparum N-Myristoyl-Transferase (PfNMT) mit relativ hoher Ausbeute und hohem Reinheitsgrad etabliert. Mehr als 500 Kristallisationslösungen wurden getestet. Unter wenigstens zwei Bedingungen konnten Anzeichen einer Kristallisation beobachtet werden, weshalb diese weiter optimiert wurden. Drittens wurde eine metabolische Markierungsmethode angewendet, um die Myristoylierung in P. falciparum zu untersuchen. Die myristoylierten Proteine in P. falciparum wurden mit einem Myristinsäureanalog metabolisch markiert und konnten durch eine sogenannte Klickreaktion biotinyliertund miteinemStreptavidin-HRP Blot detektiert werden. Mittels Avidin-Kügelchen wurden biotinylierten Zielproteine für weitere Untersuchungen (Massenspektrometrie)angereichert. Weiterhin wurden 42 mögliche myristoylierte Proteine durch das MYR-Predictor Programm und 64 Proteine durch das Myristoylator Programm vorhergesagt.
Beiträge zum Verständnis der Rolle der Adenylatkinase und Myristoylierungsreaktionen in dem Malariaparasiten Plasmodium falciparum
Keywords: adenylate kinase; myristoylation; malaria; ddc:570